Self-Reflection Program as A Future Healthcare Worker: The Smoking Cessation Experience of Health Science Students - Sutrisno, Resti Yulianti; Sarifah, Sitti Nenti; Wulandari, Bertha Tesma (Universitas Aisyah Pringsewu, 2022)
Introduction: Smoking is one of the behaviors that is a risk factor for various diseases and can cause death. Health workers have a big role in promotive and preventive as well as curative and rehabilitative efforts by controlling risk factors by advising patients not to smoke. However, it was found that health workers and health students still smoked. It is a challenge for health study program students to try to stop smoking. Research Objective: This study aims to explore the experiences of students from the Faculty of Health Sciences in an effort to stop smoking after participating in a self-reflection program on their role in the future as health workers, especially counsellors for patients. Method: This study uses a phenomenological method with an in-depth interview approach. The participants in this study were 14 undergraduate students from the Faculty of Medicine and Health Sciences. Data analysis in this study used inductive analysis. This research has passed the ethical test from the Faculty of Medicine and Health Sciences UMY. Results: There are five themes that describe participants' experiences of the self-reflection program that they have participated in 1) Mind Blowing: Contradicting the role of participants in the future as health workers with current smoking habits, 2) Awareness of inappropriate smoking behaviour for health workers, 3) Be aware of the dangers of smoking not only for yourself but also for others, 4) Increase motivation to quit smoking, 5) Gaining insight into how to quit smoking. Conclusion: A self-reflection program for smoking cessation efforts can increase motivation and help reflect on participants to stop smoking. This effort can be used as one of the counsellor’s methods in smoking cessation to help students in the health program quit smoking. Abstrak: Latar Belakang: Merokok merupakan salah satu perilaku yang menjadi fator resiko berbagai penyakit dan dapat menyebabkan kematian. Tenaga Kesehatan memiliki peran besar dalam upaya promotif dan preventif serta kuratif dan rehabilitative dengan mengendalikan factor resiko dengan menyarankan pasien untuk tidak merokok. Akan tetapi ditemukan tenaga kesehatan maupun mahasiswa kesehatan yang masih merokok. Menjadi tantangan tersendiri bagi mahasiswa program studi kesehatan untuk berupaya berhenti merokok. Tujuan Penelitian: Penelitian ini bertujuan untuk menggali pengalaman mahasiswa fakultas ilmu Kesehatan dalam upaya berhenti merokok setelah mengikuti program refleksi diri akan perannya di masa depan sebagai tenaga kesehatan khususnya konselor untuk pasien. Metode: Penelitian ini menggunakan metode fenomenologi dengan pendekatan wawancara mendalam. Partisipan dalam penelitian ini berjumlah 14 mahasiswa program sarjana Fakultas Kedokteran dan Ilmu Kesehatan. Analisis data dalam penelitian ini menggunakan induktif analisis. Penelitian ini sudah lulus uji etik dari Fakultas Kedokteran dan Ilmu Kesehatan UMY. Hasil: Terdapat lima tema yang dirasakan oleh partisipan setelah mengikuti program refleksi diri yaitu : 1) Mind blowing: mengguggah pikiran akan kontradiksi peran di masa depan sebagai konselor yang akan menyadarkan bahaya merokok dengan kondisi sekarang yang masih merokok, 2) Menyadarkan bahwa perilaku merokok tidak pantas untuk tenaga kesehatan; 3) Meningkatkan motivasi berhenti merokok; 4) Menambah wawasan metode berhenti merokok; 5) Menyadarkan bahawa merokok merugikan diri sendiri dan orang lain. Kesimpulan: Program refleksi diri sebagai upaya berhenti merokok untuk mahasiswa Kesehatan dapat meningkatkan motivasi dan membantu partisipan untuk berhenti merokok. Upaya ini dapat dijadikan sebagai salah satu cara konselor dalam upaya berhenti merokok untuk membantu mahasiswa program kesehatan berhenti merokok.